The Genetic Theory of Infectious Diseases: A Brief History and Selected Illustrations - Casanova, Jean-Laurent (Annu Rev Genomics Hum Genet, 2013)
Until the mid-nineteenth century, life expectancy at birth averaged 20 years worldwide, owing mostly to childhood fevers. The germ theory of diseases then gradually overcame the belief that diseases were intrinsic. However, around the turn of the twentieth century, asymptomatic infection was discovered to be much more common than clinical disease. Paradoxically, this observation barely challenged the newly developed notion that infectious diseases were fundamentally extrinsic. Moreover, interindividual variability in the course of infection was typically explained by the emerging immunological (or somatic) theory of infectious diseases, best illustrated by the impact of vaccination. This powerful explanation is, however, best applicable to reactivation and secondary infections, particularly in adults; it can less easily account for interindividual variability in the course of primary infection during childhood. Population and clinical geneticists soon proposed a complementary hypothesis, a germline genetic theory of infectious diseases. Over the past century, this idea has gained some support, particularly among clinicians and geneticists, but has also encountered resistance, particularly among microbiologists and immunologists. We present here the genetic theory of infectious diseases and briefly discuss its history and the challenges encountered during its emergence in the context of the apparently competing but actually complementary microbiological and immunological theories. We also illustrate its recent achievements by highlighting inborn errors of immunity underlying eight life-threatening infectious diseases of children and young adults. Finally, we consider the far-reaching biological and clinical implications of the ongoing human genetic dissection of severe infectious diseases.